Spangler, Craig interview - Emon, Ayeshah (My University, 2010)
Craig Spangler is the design principal with Ballinger in Philadelphia and one of the key architects who worked on the WID/MIR construction project. This interview documents his involvement with the early conceptualization of the Wisconsin Institutes for Discovery.